Panorama dos resíduos sólidos industriais e de mineração do estado de Goiás - Oliveira, Adjane Damasceno de (2015)
The increase the state of Goiás should come accompanied of a administration that look for the balance between economic, social and environmental sectors, In this last, it is included an appropriate management of solid waste generate at the territory. In this study was elaborated an overview of the current situation of industrial and mining solid waste, contributing directly to supply the lack of data that subsidize the elaboration of policies that strengthen the guidelines of administration in Goiás, and also contribute with the proposition of mechanisms to structure the state information system of solid waste. For this, information was collected in several databases, official (Department of the Environment, infrastructure, Cities and Metropolitan Issues, State Treasury Office, National Department of Mineral Research) and non-official (Goiás Federation of Industries) databases and a primary data collection system has been developed so that the information was as close to reality as possible. The databases accessed was compared and analyzed. To carry out the review of waste destinations was necessary some adjustment and revaluation of the coding used in the process that received these wastes. Even with the establishment of a mechanism with closed answers, it was still necessary to evaluate what was declared to carry out an overview that matches to the reality. After the data compilation, it was possible to establish results of estimative for the generation, composition and disposal of industrial and mining waste in the State of Goiás. A comparison with these results with the 2001 inventory data was carried out, and to complete the state overview, the data of the authorizations for the waste entries in the state of Goiás issued in 2013 were collected. Finally, there was an analysis of the strategic areas for installation of industrial waste centers within the state territory. According to the results obtained were estimated one generation of 8.481.680 tons of industrial waste and 10.781.011 tons of mining waste. As the destination, the destination for another forms of reuse and recycling was the most representative with almost 38% from the total of industrial waste generated, whereas, the largest portion of the mining waste was destined to landfills of the own generators of waste, approximately 75% of the total. This study demonstrated that one of the difficulties encountered in collecting information is to perform the inventory data involving the largest number of possible waste generators and allow to conclude that the results found until the time can`t be considerate satisfactory, but make a landmark for the consolidation of solid waste data collected in Goiás. Therefore it is important to promote more comprehensive training throughout the territory and the establishment of mandatory participation in data reporting. In addition, it is essential that the States and Union work together so that the databases can be compatible to the point that they can be manipulated and can produce reliable results.